Energy Management of Integrated Energy System in Large Ports - Huang, Wentao; Yu, Moduo; Li, Hao.; Tai, Nengling; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book provides a detailed exploration of energy management in seaport integrated energy systems, highlighting their potential to replace conventional fuel-based energy usage and promote sustainable development of large ports. In order to achieve carbon neutrality, energy management technologies are crucial for the sustainable development of port systems that couple energies, logistics, and maritime transportation. Research on seaport integrated energy systems has attracted scholars and scientists from various disciplines, such as port electrification, logistics, microgrids, renewable energies, energy storages, and port automation. Taking a holistic approach, this book establishes a fundamental framework for the topic and discusses the electrification process, coupling mechanisms and modeling, optimal planning, low-carbon and economic operation, as well as applications of integrated energy systems in seaports. This book is intended for researchers, graduate students,and other readers interested in green seaport energy management and low-carbon operation technologies under the coupling between logistics and multi-energy systems.
Review of Low-Carbon Technology for Integrated Port Energy Systems -- Generation of Port Microgrid Operation Scenarios for Renewable Energy and Storage Configuration -- Adaptive Bidirectional Sag Control Strategy for Hybrid Independent AC-DC Port Microgrid -- Smooth Control Strategy for Emergency Switching of Interconnected Port Microgrids via FMS -- Flexible Connected Multiple Port Microgrids Based on Hybrid Unit of Common Coupling -- Voltage Optimization Method for Port Power Supply Networks -- Hierarchical Optimization Scheduling Method for Large-Scale Reefer Loads in Ports -- Demand Side Response Considering the Discontinuity of the ToU Tariff -- Energy Cascade Utilization with Heat and Power System -- Optimal Operation of Seaport Integrated Energy Systems under Coordination between Logistic and Energy Systems -- Joint Scheduling of Power Flow and Berth Allocation in Port Microgrids -- Port Electrification and Energy Integration Cases -- Low Carbon Planning for Large Ports.
Keywords: Energy policy; Energy and state; Electric power distribution; Sustainability; Transportation engineering; Traffic engineering; Energy Policy, Economics and Management; Energy Grids and Networks; Sustainability; Transportation Technology and Traffic Engineering